Intravesical BCG in patients with non-muscle invasive bladder cancer induces trained immunity and decreases respiratory infections - J Alfred Witjes; Alina Vrieling; Mihai G Netea; Leo A B Joosten; Katja K H Aben; Sita H Vermeulen; Joost L Boormans; Antoine G van der Heijden; Boris Novakovic; Jelmer H van Puffelen; Liesbeth van Emst; Denise Kooper; et al. (Journal for ImmunoTherapy of Cancer)
Background BCG is recommended as intravesical immunotherapy to reduce the risk of tumor recurrence in patients with non-muscle invasive bladder cancer (NMIBC). Currently, it is unknown whether intravesical BCG application induces trained immunity.Methods The aim of this research was to determine whether BCG immunotherapy induces trained immunity in NMIBC patients. We conducted a prospective observational cohort study in 17 NMIBC patients scheduled for BCG therapy and measured trained immunity parameters at 9 time points before and during a 1-year BCG maintenance regimen. Ex vivo cytokine production by peripheral blood mononuclear cells, epigenetic modifications, and changes in the monocyte transcriptome were measured. The frequency of respiratory infections was investigated in two larger cohorts of BCG-treated and non-BCG treated NMIBC patients as a surrogate measurement of trained immunity. Gene-based association analysis of genetic variants in candidate trained immunity genes and their association with recurrence-free survival and progression-free survival after BCG therapy was performed to investigate the hypothesized link between trained immunity and clinical response.Results We found that intravesical BCG does induce trained immunity based on an increased production of TNF and IL-1β after heterologous ex vivo stimulation of circulating monocytes 6–12 weeks after intravesical BCG treatment; and a 37% decreased risk (OR 0.63 (95% CI 0.40 to 1.01)) for respiratory infections in BCG-treated versus non-BCG-treated NMIBC patients. An epigenomics approach combining chromatin immuno precipitation-sequencing and RNA-sequencing with in vitro trained immunity experiments identified enhanced inflammasome activity in BCG-treated individuals. Finally, germline variation in genes that affect trained immunity was associated with recurrence and progression after BCG therapy in NMIBC.Conclusion We conclude that BCG immunotherapy induces trained immunity in NMIBC patients and this may account for the protective effects against respiratory infections. The data of our gene-based association analysis suggest that a link between trained immunity and oncological outcome may exist. Future studies should further investigate how trained immunity affects the antitumor immune responses in BCG-treated NMIBC patients